Reconstruction of Atomistic Models of Dislocations by Means of Finite Deformation Theory - DŁUŻEWSKI, Paweł; NALEPKA, Kinga (Computer Assisted Methods in Engineering and Science, 2025)
The present paper discusses mathematical barriers in the development of software for preprocessing of atomistic models of dislocation networks. As a matter of fact, as yet, there are neither analytical nor numerical methods nor programs available which can be used for atomistic reconstruction of complex dislocation networks. Some of the problems to overcome are discussed in this paper. In the previous papers discussed below it was shown that a direct superposition of analytic formulae for displacements of atoms induced by single dislocations does not give possibility to hold the essential geometric properties of the resultant atomistic models. Namely, after the input of first dislocation, the lattice symmetry required to input the next dislocations is usually broken. These inaccuracies compose the mathematical barrier for atomistic reconstruction of advanced dislocation nets. A method developed here has been applied to reconstruction of the dislocation nodes localized in the copper/shaffire interface. In the present case, the partial dislocations are inserted by slips. For comparison, the junction corresponding to the stacking faults obtained by the rigid shifts of copper on the Burgers vector  1/6 are discussed.